Investigating Indian Agribusiness Competitiveness with Gulf Nation Using Constant Market Share Analysis - Mohd Shadab Khan, Saghir Ahmad Ansari, Mohd Fateh, (European Economic Letters (EEL), 2024)
Purpose - This study examines the Indian agribusiness competitiveness and market share analysis of Indian gribusiness products in the market of The Gulf Cooperation Council countries – United Arab Emirates, Saudi Arabia, Bahrain, Kuwait, Oman and Qatar. Design/methodology/approach - The data is investigated using constant market share analysis introduced by tysznskin and Richardson. The data period is taken from 2011 and 2021. The Commodity Composition Effect (CCE), World Demand Effect (WDE), Market Demand Effect (MDE), and Residual Competitiveness Effect (RCE) are the four effects that make up the Constant Market Share Analysis (CMSA) model, which is used to analyze structural changes in international trade. Findings - The study found that World Demand Effect (WDE) is positive and very high so WDE is the main reason for potential growth in exports of these Agri related products to gulf cooperation. Commodity composition effect and market distribution effect is negative .so cce and mde contribution in growth is less. Residual competitiveness effect is positive and high. so it contributes to the growth. COMPETITIVENESS of a products is measure by using World Demand Effect (MDE),Market Distribution Effect (MDE), Commodities Composition Effect(CCE)and residual effect (competitiveness effect). In this paper agribusiness is focused. the data is taken from the site i.e. OEC observatory of economic complexity. Data is secondary in nature. Competitiveness of products is analysed. The product categories are vegetables, foodstuff, animal product and animal and vegetables biproducts. Market share of Qatar, Bahrain, and Saudi Arabia was increased. UAE, Oman, and Kuwait market share were decreased during this period. World percent share increases by 1.28%. VEGETABLES PRODUCTS: - MDE is negative in nature. FOODSTUFFS: -WDE and competitiveness effect is positive in nature. ANIMAL PRODUCT: - CCE is negative. ANIMAL AND VEGETABLES BI-PRODUCTS: -MDE is negative in nature. In the highly competitive global marketplace, India has emerged as a major player in agricultural exports. The economic significance of the country's agricultural sector cannot be overstated, as it contributes significantly to the nation's GDP and plays a important role in providing livelihoods to a large portion of the population. This paper aims to examine competitiveness in Indian agriculture, this review seeks to uncover the key strengths and weaknesses of the sector, while also identifying potential opportunities and threats. Factors such as government policies, technological advancements, infrastructure development, market access, and global demand for agricultural produce will be explored in detail. Practical implications -The results finds that Agricultural product is one of the major export products to gulf corporation. In this study the four categories of product are vegetables products, foodstuffs, animal products, animal and vegetable Bi- products. The value of these products in 2011 was $ 31.42 billion and in 2021 was $ 48.39 billion. share of India’s exports in world exports (%). In 2011 vegetables products (3.35), foodstuffs (1.51), animal products (1.86), animal and vegetable Bi- products (1.17).In 2021 vegetables products(3.73), Foodstuffs (1.64), animal products (2.49) and animal and vegetable Bi- products (1.30). Originality/value -The uniqueness of this paper lies in its focus countries that is GULF CORPORATION and INDIA, A Constant Market Share Analysis is used to analyse the competitiveness of Indian agribusiness.